ANALISIS RISIKO PRODUKSI KARET RIBBED SMOKED SHEET (STUDI KASUS DI KEBUN MERBUH, PTPN IX ) - Iandri Dapa Mede, Abraham; Roessali, Wiludjeng; Nurfadilah, Suryani (JURNAL LITBANG PROVINSI JAWA TENGAH, 2021)
Ribbed Smoked Sheet Rubber is Indonesia’s leading export product. PTPN IX is one of the state-owned companies that also processes latex into RSS, but still faces many obstacles in its production process caused by various factors. This study aimed to analyze: 1). RSS production quantity, 2). RSS production quality, 3). level of production risk, 4). primary risk that cause failure, and 5). mitigation strategies to minimize the impact of production risks. The research was conducted from February to April 2021 at Merbuh Plantation, PTPN IX Trayu Village, Singorojo District, Kendal Regency. This research used the case study method. Data was analyzed using descriptive quantitative methods include Coefficient of Variation (CV) and Fuzzy Failure Mode and Effect (Fuzzy FMEA). The results showed that the level of risk in the RSS factory Merbuh Plantation is classified as very high with 24% of CV. There were 3 main risks out of 17 identified risks with the highest FRPN value, i.e.: aluminum insulation damage (8.74), dry rubber content is not up to standard (7.63), and early upregulation of latex with (6.87). Risk mitigation in disciplinary aspects, labor aspects, and technical aspects needs to be implemented in order to reduce risk.